Pelatihan Pembuatan Lilin Aromaterapi Ekstrak Serei Wangi dari Lilin Parafin Melalui Metode Demonstrasi Terbimbing Untuk Meningkatkan Kreativitas Remaja Karang Taruna Di Kelurahan Habaring Hurung - Maradona Maradona; Noor Hujjatusnaini (Edumedia Solution, 2022)
Creativity is needed in social life, one of the goals is to build youth creativity. Training on making aromatherapy candles is one way to increase the creativity and innovation of young entrepreneurs that are worth selling. This training was carried out in Habaring Hurung Village, Bukit Batu District, with a guided demonstration method. The purpose of this training is so that youth youth groups in Habaring Hurung Village can understand the theory and practice of making aromatherapy candles, have the opportunity to develop more creative small industries, so that they can play an important role in the advancement of youth productivity and entrepreneurial spirit in Habaring Hurung Village. The results of this training activity showed that there was a significant increase in 80% of the overall activities. It can be said that the training activities for making aromatherapy candles were successfully carried out.